Guidelines for organizing social welfare for the elderly in the border regions, Mae la sub-district, Tha Song Yang district, Tak province - sangkarat, patthayaporn (Huachiew Chalermprakiet Law Journal, 2024)
A study of guidelines for providing social welfare for the elderly in marginal areas, Mae La Subdistrict, Tha Song Yang District, Tak Province. The objective is to study access to welfare for the elderly and guidelines for providing welfare for the elderly in marginal areas, Mae La Subdistrict, Tha Song Yang District, Tak Province, is qualitative research using in-depth interviews. The results of the study found that 1) Access to the welfare of the elderly in Mae La Subdistrict, Tha Song Yang District, Tak Province, 50 percent of the elderly had access to various welfare benefits such as elderly living allowances, health promotion services, participation in various activities of regional agencies. government, but some elderly people do not have access to welfare in the following areas: (1) traveling for the elderly because it is a marginal and remote area, therefore causing problems in accessing welfare (2) characteristics of the elderly Related to the attitude of the elderly, not going out into society, some people having health conditions Have a congenital disease that prevents them from accessing government social services. (3) Government agencies and social welfare officials for caring for the elderly are insufficient. (4) The budget allocated by the government is insufficient to provide welfare. 2) Guidelines for providing welfare for the elderly in marginal areas, Mae La Subdistrict, Tha Song Yang District, Tak Province, can be summarized as follows: (1) Promoting the elderly individually, accepting them, appreciating them and promoting their potential, supporting them in health, housing and the environment, organizing social activity programs, creating opportunities for the elderly to have opportunities, to participate in social activities, develop a quality care service system, support work, provide psychological services. 2) Management of the Mae La Subdistrict Administrative Organization, personnel must know and understand the nature of the elderly, allowing volunteers to take care of the elderly, and operational processes. There should be work planning, operations consistent with the workload, continuous supervision, and monitoring, budget allocation from the government is insufficient, funding should be provided, external donations and difficult travel should be provided. Budget for transportation for the elderly or facilitation of travel. or there is a budget allocation from organizations within the private sector for support, etc.